Printing Parameter Optimization of Flexible Strain Sensor for Maximum Strain Level Analysis - Faiq Ramadhani; Wangi Pandan Sari (Universitas Atma Jaya Yogyakarta, 2026)
This study explores the optimization of printing parameters for Flexible Strain Sensors (FSS) produced using fused deposition modeling. The experimental design utilizes a Taguchi L18 orthogonal array to assess the impact of five parameters—substrate material, sensor thickness, printing temperature, printing speed, and layer height—on the maximum tensile strain (elongation at break) of the printed sensors. The findings indicate that thermoplastic polyurethane (TPU) significantly enhances strain capability compared to polylactic acid (PLA). The optimal parameter combination consists of a sensor thickness of 0.3 mm, a printing temperature of 210 °C, and a printing speed of 40 mm/s, with variations in layer height having a minimal influence. Validation testing confirmed the optimization results, achieving a maximum tensile strain of 26.3% with strong agreement between predicted and experimental responses.